A brainstem-to-mediodorsal thalamic pathway mediates sound-induced arousal from slow-wave sleep - Shin, Anna; Park, Seahyung; Shin, Wooyeon; Woo, Jeonghoon; Jeong, Minju; Kim, Jeongjin; Kim, Daesoo (Cell Press, 2023)
Auditory-induced arousal is a defense mechanism of animals against potential dangers. Although the thal-amus is the neural substrate that relays sensory information to the cortex, its function is reduced during slow-wave sleep (SWS), also known as deep sleep. Despite this, animals are capable of waking up in response to external sensory stimuli, suggesting the existence of neural circuits that are involved in this response. Here, we report that kainate-class-type ionotropic glutamate receptor subunit 4 (GRIK4)-positive mediodorsal (MD) thalamic neurons act as a neural substrate for arousals from SWS. These neurons become active during arousal from SWS and their photoactivation can induce arousal from SWS. Moreover, we show that these neurons are influenced by glutamatergic neurons in the brainstem, the activity of which increases during auditory-induced arousals. These results suggest that this brainstem-MD pathway can mediate wake-fulness from SWS.